Facilitating the acidic oxygen reduction of Fe–N–C catalysts by fluorine-doping. Issue 1 (11th November 2021) - Tao, Xiafang; Lu, Ruihu; Ni, Lingmei; Gridin, Vladislav; Al-Hilfi, Samir H.; Qiu, Zijie; Zhao, Yan; Kramm, Ulrike I.; Zhou, Yazhou; Müllen, Klaus
Abstract : We report a F-doped FeNC catalyst with improved ORR performance. The enhanced performance is associated with the large BET surface area, abundant single Fe atoms, and strong electron-withdrawing F-doping. Abstract : As the alternatives to expensive Pt-based materials for the oxygen reduction reaction (ORR), iron/nitrogen co-doped carbon catalysts (FeNC) with dense FeN x active sites are promising candidates to promote the commercialization of proton exchange membrane fuel cells. Herein, we report a synthetic approach using perfluorotetradecanoic acid (PFTA)-modified metal–organic frameworks as precursors for the synthesis of fluorine-doped FeNC (F-FeNC) with improved ORR performance. The utilization of PFTA surfactants causes profound changes of the catalyst structure including F-doping into graphitic carbon, increased micropore surface area and Brunauer–Emmett–Teller (BET) surface area (up to 1085 m 2 g −1 ), as well as dense FeN x sites. The F-FeNC catalyst exhibits an improved ORR activity with a high E 1/2 of 0.83 V ( vs . RHE) compared to the pristine FeNC material ( E 1/2 = 0.80 V). A fast decay occurs in the first 10 000 potential cycles for the F-FeNC catalyst, but high durability is still maintained up to another 50 000 cycles. Density functional theory calculations reveal that the strongly withdrawing fluorine atoms doped on the graphitic carbon can optimize the electronic structure of the FeN x active center and decrease the adsorption energy of ORR intermediates.